Unskilled Workers in an Economy with Skill-Biased Technology - Shouyong Shi (Queen's University, Department of Economics, 1999)
This paper contributes to the search theory of unemployment by endogenously deriving matching functions and surplus sharing rule for skilled and unskilled workers from a wage-posting game. In contrast to previous wage posting models, here both sides of the market are heterogeneous and the resulted matching function can exhibit non-constant returns to scale. The model provides useful explanations for the observed dynamic patterns of within-skill and between-skill wage differentials in the 1970s and 1980s.
Keywords: C78; J31; J64; 330; Wage posting; Wage differential; Matching; Technological progress